Pre-Negotiation Activities: A Study of the Main Activities Undertaken by the Negotiators as Preparation for Negotiation - Balliu, Teuta; Spahiu, Artan (European Journal of Economics and Business Studies, 2020)
The most part of the researches has largely been focused on what happens at the negotiation table, rather than in its preparation and planning. Through this paper we will try to underline the importance of the preparation and planning activities which are necessarily undertaken in a business negotiation. For this purpose, we have reviewed the negotiation literature regarding these pre-negotiation processes and the necessary activities for each of them. One of the most important concerns is the extent to which the negotiators follow the literature recommendations about pre-negotiation processes. This is a quantitative research design which tries to collect data, through interviews and a questioner designed for it and makes analyzes and logical deductions on the results achieved. The results of this study derive from a questioner with 68 respondents, who provide an understanding of the preparation and planning activities they conduct as part of their negotiations. This study finds out that the negotiators follow the most important activities which are suggested by the negotiation literature. It is literally understandable that the preparation and planning processes precede the negotiation, which means that they are conducted generally before the meeting between the negotiating parties. In fact, even this study shows that these activities occur not only before a meeting but also after it, as the first step in preparing for the next meeting. In this regard we suggest seeing the preparation and planning not as a single event, but as cyclical processes. These findings can be used by business negotiators and by different companies.
Keywords: negotiation, preparation, planning, activities.